Integrating qualitative research methods into care improvement efforts within a learning health system: addressing antibiotic overuse. Issue 1 (December 2016) - Munoz-Plaza, Corrine; Parry, Carla; Hahn, Erin; Tang, Tania; Nguyen, Huong; Gould, Michael; Kanter, Michael; Sharp, Adam
Abstract Background Despite reports advocating for integration of research into healthcare delivery, scant literature exists describing how this can be accomplished. Examples highlighting application of qualitative research methods embedded into a healthcare system are particularly needed. This article describes the process and value of embedding qualitative research as the second phase of an explanatory, sequential, mixed methods study to improve antibiotic stewardship for acute sinusitis. Methods Purposive sampling of providers for in-depth interviews improved understanding of unwarranted antibiotic prescribing and elicited stakeholder recommendations for improvement. Qualitative data collection, transcription and constant comparative analyses occurred iteratively. Results Emerging themes and sub-themes identified primary drivers of unwarranted antibiotic prescribing patterns and recommendations for improving practice. These findings informed the design of a health system intervention to improve antibiotic stewardship for acute sinusitis. Core components of the intervention are also described. Conclusion Qualitative research can be effectively applied in learning healthcare systems to elucidate quantitative results and inform improvement efforts.